TINJAUAN FIQH MUAMALAH TERHADAP PEMAKAIAN SISTEM PAY LATER DALAM APLIKASI JUAL BELI ONLINE SHOPEE - Witry Octasary Aritonang (Al-Iqtishad: Jurnal Ekonomi Syariah, 2022)
In the era of technology that continues to develop over time, online services are created to meet the needs of human life, making all the necessities of life easy to fulfill, such as one of the online buying and selling services in an application called Shopee. from food, clothing, to household appliances and others, and for users of this application, it is no stranger to one of the systems offered by Shopee to pay for purchased goods, where Shopee makes the "Pay Later" feature or also called SpayLater, which means that the payment can be made without having to pay immediately for the goods purchased or also called the credit system, which of course is based on the terms and conditions that apply in the SPay Later system. The type of data that will be used in this research is qualitative data, namely data in the form of words or sentences. Qualitative data is obtained by conducting documentation studies and/or literature studies from various sources. The data source that will be used is a secondary data source, namely by processing and analyzing existing sources in the form of journals, articles, reports, and other information related to the Fiqh Muamalah Review and the basic principles of Fiq Muamalah on the credit system carried out in buy and sell. The purpose of this study is to find out how Fiqh Muamalah reviews the credit system offered by Shopee through its feature called SPayLater. The results of this study indicate that the use of the SPayLater credit system in the Fiqh Muamalah review is permissible (mubah) this is caused by the contract which is carried out clearly, which can be proven through the existing contract agreement between the seller and the buyer when carrying out the consent and Kabul as well as additional the agreed price on the SPayLater credit system as a deferral fee. However, the system using SPayLater in the Shopee online buying and selling application is prohibited when there is interest that must be paid by the buyer if he does not pay according to the correct tempo, in this case the SPayLater user will be charged interest and other fees, which is at least 5 % for payment of bills.